Historia de la medicina en Colombia. Hacia una profesión Liberal -1865 - 1918-. Tomo III. (2020)
Reseña bibliográfica; Autores: Quevedo E., Pérez GE, Miranda N., Eslava JC., Hernández M., et al. -2010- Tecnoquímicas, S.A. Ed. Norma. ISBN 978-958-45-2164-4.